Does human capital pay? The influence of leader human capital and employee human capital on leader bonus earnings. Issue 1 (13th November 2020) - Harris, Christopher M.; Brown, Lee W.
Abstract : Purpose: The human capital of a leader and the human capital of the employees who work for the leader can impact the bonus earned by the leader. Little to no research has examined data that includes the maximum potential bonus that could be earned by a leader and the actual bonus earned. This information provides a closer examination of leader performance and the impacts of leader and employee human capital on the bonus earned by the leader. Design/methodology/approach: The authors use a sample of NCAA college football teams and head coaches over two years to test their hypotheses. They measure the human capital of the team and the human capital of the head coach. In addition, the authors assess the percentage earned by the head coach of the maximum potential bonus possible. Findings: The authors find that a coach's human capital and the human capital of their team positively and significantly predict the percentage of the maximum possible bonus earned by the head coach. Practical implications: The results of this study indicate the importance of leader human capital to a leader's ability to earn more of their maximum potential bonus. Additionally, if a leader is able to surround himself or herself with highly talented employees, it will benefit the leader in terms of the amount of bonus earned. Originality/value: This study extends previous research to provide a more complete picture of factors that influence a leader's ability to earn more of their maximum possible bonus. The authors' findings that both the human capital of the leader and the human capital of employees who work for the leader impact the amount of bonus earned by the leader add value to human resource management research. Specifically, when examining factors that impact a leader's bonus earnings, it is important to consider not only characteristics of the leader but also factors apart from the leader, such as the leader's employees.